Advances in targeted alpha therapy for prostate cancer. (16th August 2019) - De Vincentis, G; Gerritsen, W; Gschwend, J E; Hacker, M; Lewington, V; O'Sullivan, J M; Oya, M; Pacilio, M; Parker, C; Shore, N; Sartor, O; ,
Abstract: Amongst therapeutic radiopharmaceuticals, targeted alpha therapy (TαT) can deliver potent and local radiation selectively to cancer cells as well as the tumor microenvironment and thereby control cancer while minimizing toxicity. In this review, we discuss the history, progress, and future potential of TαT in the treatment of prostate cancer, including dosimetry-individualized treatment planning, combinations with small-molecule therapies, and conjugation to molecules directed against antigens expressed by prostate cancer cells, such as prostate-specific membrane antigen (PSMA) or components of the tumor microenvironment. A clinical proof of concept that TαT is efficacious in treating bone-metastatic castration-resistant prostate cancer has been demonstrated by radium-223 via improved overall survival and long-term safety/tolerability in the phase III ALSYMPCA trial. Dosimetry calculation and pharmacokinetic measurements of TαT provide the potential for optimization and individualized treatment planning for a precision medicine-based cancer management paradigm. The ability to combine TαTs with other agents, including chemotherapy, androgen receptor-targeting agents, DNA repair inhibitors, and immuno-oncology agents, is under investigation. Currently, TαTs that specifically target prostate cancer cells expressing PSMA represents a promising therapeutic approach. Both PSMA-targeted actinium-225 and thorium-227 conjugates are under investigation. The described clinical benefit, safety and tolerability of radium-223 and the recent progress in TαT trial development suggest that TαT occupies an important new role in prostate cancer treatment. Ongoing studies with newer dosimetry methods, PSMA targeting, and novel approaches to combination therapies should expand the utility of TαT in prostate cancer treatment.